Lymphatic Filariasis Control: School-based One Health Initiative on The Usage of Local Plants as Alternative Mosquito Repellants in Timor Tengah Selatan, Nusa Tenggara Timur - Gelolodo, Maria Aega; Almet, Julianty; Detha, Annytha I. R (International Journal of Community Service Learning, 2022)
Lymphatic filariasis is a mosquito-borne disease that poses a serious public health concern. The disease has spread to 28 Indonesian provinces, with NTT province being one of the 10 provinces with the highest incidence. Aside from being a major supporter of the annual mass drug administration program, the mosquito control initiative is also critical to the disease's eradication. However, today's mosquito control approaches depend primarily on synthetic moieties, which, unfortunately, have resulted in environmental problems and also resistance in important mosquito species. Consequently, developing alternative mosquito control strategies based on herbal components that are environmentally friendly, safe, and long-lasting is necessary. This one-health program aims to educate and raise public awareness of the importance of mosquito control and to inspire the community to utilize local plants as alternative mosquito repellents. This program is targeted high school students from the Timor Tengah Selatan regency. This regency is one of the NTT regencies with the highest risk of lymphatic filariasis. The approach method employed in this program was a series of presentations, discussions, and a demonstration of lymphatic filariasis and the selection of local plants that can be used as herbal repellents. Based on discussions with the students, it was discovered that after engaging in this activity, the participants had learned and recognized the dual function of various indigenous plants in their area as effective and cost-effective mosquito repellents. Furthermore, the students became more excited to learn and develop knowledge about the function of other local plants as efficient mosquito repellents.